-2(4x+1)=2(-4x-1)

Simple and best practice solution for -2(4x+1)=2(-4x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4x+1)=2(-4x-1) equation:


Simplifying
-2(4x + 1) = 2(-4x + -1)

Reorder the terms:
-2(1 + 4x) = 2(-4x + -1)
(1 * -2 + 4x * -2) = 2(-4x + -1)
(-2 + -8x) = 2(-4x + -1)

Reorder the terms:
-2 + -8x = 2(-1 + -4x)
-2 + -8x = (-1 * 2 + -4x * 2)
-2 + -8x = (-2 + -8x)

Add '2' to each side of the equation.
-2 + 2 + -8x = -2 + 2 + -8x

Combine like terms: -2 + 2 = 0
0 + -8x = -2 + 2 + -8x
-8x = -2 + 2 + -8x

Combine like terms: -2 + 2 = 0
-8x = 0 + -8x
-8x = -8x

Add '8x' to each side of the equation.
-8x + 8x = -8x + 8x

Combine like terms: -8x + 8x = 0
0 = -8x + 8x

Combine like terms: -8x + 8x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 3(3x-7)=2(3x+10) | | 9-2+7x=9+3x+2 | | x^3+13x^2+3x+10=0 | | 7x+8=18+5x | | (6+3x)2=48 | | 32+x=74-2x | | (4+2x)5=70 | | 16-2x=30-4x | | (4x-2)3=30 | | 1790=0.04x | | 2x/5x= | | 52=r*26 | | 2(5x+14)=33 | | -8(t-2)-(t+4)=9 | | 2x=7x-25 | | 3x=5x-1 | | 1.9=0.05x-98.40 | | 10-0.25(x+4)=0 | | 8x+15=5x | | 2002=0.05x-98.40 | | n=-98.40+0.05x | | 01x+32=85 | | x^2-5x-14=-10 | | y^2+3y-10=10 | | 4w(4w-3)=1-12w | | 7x-12=x+36 | | 35=-5t^2+10t+75 | | y^2-10y-8x+1=0 | | 6(x+.5)=x+8 | | 123+56=347 | | 9n-21=60 | | 8+6(2x-1)= |

Equations solver categories